إستراتيجية التقييم الشامل في تعليم التربية الإسلامية الموجّه إلى إنشاء الشخصية الكاملة - Agus Zainul Fitri (Jurnal Pendidikan Islam, 2014)
[Teacher has a very heavy duty, but of the many duties of teachers, the assessment is the most difficult aspect. This happens not because of the weakness of teachers in evaluating learning outcomes in schools, because of the demands imposed on him, namely that learners must pass in learning, especially in the National Exam. This research is a kind of field research with qualitative approach to engineering design multisitus collecting data through interviews, participant observation and document study. The results of this study indicate that the strategy adopted in order to authentic assessment in the form private PAI holistic done through: (1) the transparency of the system in the initial assessment of learning; (2) the manufacture of diary; (3) specific code generation; (4) development of peer tutoring as an appraiser; (5) record makers "Anecdotes"; and (6) changes in the paradigm of teachers and parents. While the problems facing the PAI authentic assessment, namely: (1) the demands of the KKM, (2) the demands of school leaders and parents, (3) the demands of further education, (4) not achieving the standard of learning PAI on previous education, (5) has not been a real learning process, (6) lack of exemplary teachers, and (7) lack of time studying PAI in school].